2015
DOI: 10.5483/bmbrep.2015.48.12.106
|View full text |Cite
|
Sign up to set email alerts
|

An inhibitory alternative splice isoform of Toll-like receptor 3 is induced by type I interferons in human astrocyte cell lines

Abstract: Toll-like receptor 3 (TLR3) recognizes viral double-stranded RNA. It stimulates pro-inflammatory cytokine and interferon production. Here we reported the expression of a novel isoform of TLR3 in human astrocyte cell lines whose message is generated by alternative splicing. The isoform represents the N-terminus of the protein. It lacks many of the leucine-rich repeat domains, the transmembrane domain, and the intracellular Toll/interleukin-1 receptor domain of TLR3. Type I interferons (interferon-α and interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…B) pathways play an essential role in TLR3‐mediated gene induction . The loss of inflammation response of cells to bacterial (LPS) or viral (Poly (IC) infection has been shown before in specific mouse neural cell types that overexpress a different mutant mouse TLR3 isoform to the human TLR3 isoform described in this study (not expressed in mice) . Interestingly, a recent study found that differentiation of human iPSC results in a loss of immunogenicity and leads to the induction of tolerance, despite expected antigen expression differences between iPSC‐derived versus original somatic cells .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…B) pathways play an essential role in TLR3‐mediated gene induction . The loss of inflammation response of cells to bacterial (LPS) or viral (Poly (IC) infection has been shown before in specific mouse neural cell types that overexpress a different mutant mouse TLR3 isoform to the human TLR3 isoform described in this study (not expressed in mice) . Interestingly, a recent study found that differentiation of human iPSC results in a loss of immunogenicity and leads to the induction of tolerance, despite expected antigen expression differences between iPSC‐derived versus original somatic cells .…”
Section: Discussionsupporting
confidence: 54%
“…Given that it has been previously published that a short isoform of mouse TLR3, but different sequence and size to the human TLR3 isoform described in this study can act as a suppressor of the TLR3 innate immune pathway by competing with the full length TLR3 protein in mouse astrocytes , we next assessed the functional immune response of inflammation cytokine IL6 in human iPSC‐NSC to Poly (I:C) and LPS. Assessment of IL6 expression levels by ELISA demonstrated that iPSC‐derived cells (F2 cells) have significantly higher levels of expression of IL6 compared to F1 cells and a suppressed innate immune response to viral infection (Poly IC 1ug/ml overnight) in iPSC‐derived cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cotreatment with the ginsenoside Rh3 markedly decreased cisplatin-induced phosphorylation of JNK and ERK MAPKs (Fig. 2) that are well defined representative inflammation markers [21], [22]. Recently, ginsenoside Rh3 was reported to inhibit the expressions of inducible nitric oxide synthase (iNOS) and proinflammatory cytokines (tumor necrosis factor (TNF)-α and interleukin (IL)-6) in lipopolysaccharide-stimulated microglia [21].…”
Section: Resultsmentioning
confidence: 89%
“…At the same time, celastrol was not able to reduce poly(I:C)-induced phosphorylation of ERK and p38, but it rather led to increased phosphorylation of ERK and p38 MAPKs in the treated cells. Previous studies reported JNK mediating poly(I:C)-induced activation of STAT1 ( 17 , 18 ), with poly(I:C) stimulation, STAT1 transcription factor plays a significant role in the expression of various pro-inflammatory mediators in astrocytes ( 7 , 8 , 19 ). Therefore, we next investigated the effect of celastrol on poly(I:C)-induced STAT1 activation.…”
Section: Resultsmentioning
confidence: 95%